2014
DOI: 10.5116/ijme.52e3.a465
|View full text |Cite
|
Sign up to set email alerts
|

Depression and suicidal ideation in medical students in China: a call for wellness curricula

Abstract: ObjectivesTo investigate rates of depression and suicidal ideation in medical students in mainland China and to explore wellness curricula and mental health services available to students.MethodsSecond and third year medical students (N=348) at one medical school in mainland China completed the Patient Health Questionnaire-9 (PHQ-9). Based on responses to the PHQ-9, students were labeled as depressed, with suicidal ideation, and/or impaired. Additionally, students’ feedback from a focus group (N=30) evaluating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
77
3
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 33 publications
12
77
3
11
Order By: Relevance
“…The primary goal of this study was to establish mental health status and attitudes towards suicide as predictors of suicidal ideation among a sample of Chinese children and adolescents. In line with previous studies, which indicate that attitudes towards suicide and mental health are significant predictors of suicidal ideation in young and older adult samples (Limbacher & Domino ; Stack & Wasserman ; Gutierrez et al ; Caldwell et al ; Gibb et al ; Joe et al ; Salander et al ; Hintikka et al ; Nurka & Amila ; Amanda et al ; Milner et al ; Sobowale et al ), the current study replicated these findings and showed that the effects are also evident in the present children and adolescent sample. Specifically, attitudes towards suicide and mental health were found to account for an additional 15.1% of variance in suicidal ideation beyond what was accounted for by demographic variables.…”
Section: Discussionsupporting
confidence: 92%
“…The primary goal of this study was to establish mental health status and attitudes towards suicide as predictors of suicidal ideation among a sample of Chinese children and adolescents. In line with previous studies, which indicate that attitudes towards suicide and mental health are significant predictors of suicidal ideation in young and older adult samples (Limbacher & Domino ; Stack & Wasserman ; Gutierrez et al ; Caldwell et al ; Gibb et al ; Joe et al ; Salander et al ; Hintikka et al ; Nurka & Amila ; Amanda et al ; Milner et al ; Sobowale et al ), the current study replicated these findings and showed that the effects are also evident in the present children and adolescent sample. Specifically, attitudes towards suicide and mental health were found to account for an additional 15.1% of variance in suicidal ideation beyond what was accounted for by demographic variables.…”
Section: Discussionsupporting
confidence: 92%
“…Twenty-four cross-sectional studies (n = 21 002) in 15 countries reported on the prevalence of suicidal ideation (Table 2). 4,5,34,62,65,73,74,79,112,160,165,167,174,[185][186][187][188][189][190][191][192][193][194][195] Medical student training level, continent or region, country, diagnostic criteria or screening instrument cutoff, and total Newcastle-Ottawa scores for the studies appear in eTable 1 in the Supplement. Newcastle-Ottawa score components for all 195 individual studies appear in eTable 2 in the Supplement.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A recently conducted Chinese study reported 7.5% suicidal ideation among medical students. This figure can go high up to 30% in depressed students (Sobowale K et al, 2014). Studies have also reported suicidal ideation among medical students.…”
Section: Discussionmentioning
confidence: 94%